Targeting Stimulator of Interferon Genes (STING): A Medicinal Chemistry Perspective - Zhang, Han; You, Qi-Dong; Xu, Xiao-Li (Journal of medicinal chemistry, 2020)
Stimulator of interferon genes (STING) is an adaptor protein that induces the secretion of type I interferons and proinflammatory cytokines and is triggered by cytosolic DNA of pathogen and host origins. Given that STING is a mediator in the immune system, pharmacological modulation of STING has shown viable therapeutic effects for pathogen infection, cancer, and inflammatory diseases. In the past decade, the substantial development in this field has encouraged the discovery of STING modulators. Here, we will summarize the current understanding of STING structure, survey the status quo of STING modulators, compare established bioassay methods, review the chemical structures and bioactivities of agonists and inhibitors, and propose suggestions and insights for the future exploitation of STING modulators.